Bioleaching of metal(loid)s from sulfidic mine tailings and waste rock from the Neves Corvo mine, Portugal, by an acidophilic consortium. (October 2022) - Opara, Chiamaka Belsonia; Blannin, Rosie; Ebert, Doreen; Frenzel, Max; Pollmann, Katrin; Kutschke, Sabine
Highlights: Bioleaching is an important technique for the reprocessing of sulfidic mine wastes. Acidophilic microbial consortium can simultaneously recover both valuable and hazardous elements from pyrite-rich waste rock and tailings. XRD and SEM/MLA reveal mineralogical transformations after microbial-leaching. Jarosite was the main secondary mineral formed after bioleaching. Potential for revenue generation and environmental risk reduction at the Neves Corvo mine, Portugal. Abstract: Sulfidic mine waste usually contains elevated amounts of valuable and hazardous metal(loid)s, which may pose environmental risks but can also provide opportunities for resource recovery. Reprocessing of mine waste can offer both economic and environmental benefits by supplying some of the ever-growing global demand for valuable metals, as well as reducing environmental risks. The present study aimed to simultaneously recover both valuable and hazardous metal(loid)s from two sulfidic mine waste samples (waste rock (NC_01) and tailings (NC_02)) from the Neves Corvo mine, Portugal, using a novel acidophilic consortium dominated by iron-oxidizing Leptospirillum genus and Acidiphilium sp . Bioleaching results showed that over 70% of the total Zn, Co, In, As, and Cd contents of NC_01 and NC_02 were leached within 21 days, while 55%–62% Mn was leached. Copper behaved in a refractory manner, as only 33% and 21% Cu were leached from NC_01 and NC_02, respectively. X-ray diffraction (XRD) and Scanning electron microscope-based automated image analyses (SEM/MLA-GXMAP) of the bioleached residues revealed an almost complete absence of residual pyrite in NC_01 and a reduction of pyrite in NC-02, as well as the formation of secondary minerals, especially jarosite. In most cases, the biogenic jarosite co-precipitated some of the leached elements again, e.g., Cu and Pb. In conclusion, a synchronized method for bioleaching valuable and hazardous metal(loid)s was developed using a novel acidophilic consortium, thereby demonstrating the potential for the generation of economic value and environmental risk reduction for sulfidic mine waste samples.